Locus of Control and Consistency of Measured Vocational Interests - Hughson, Joyce; Foster, James (Canadian Journal of Counselling and Psychotherapy, 2012)
The study examined the relationship between Rotter's (1966) concept of locus of control and certain constructs from Holland's (1966) theory.The Kuder DD Occupational Interest Survey (OIS) and Rotter's I-EScale were administered to 162 freshmen male students at Acadia University.Primary and secondary vocational types, and consistent and inconsistent patterns were established from the OIS following Holland'sclassification system. Intellectual and Realistic types differed significantly at the .05 and .01 level respectively from the remaining four vocational types in the direction of greater external control. Individuals with consistent patterns were significantly (.05 level) more internally controlled than those with inconsistent patterns. Le but de notre étude était d'examiner les relations existant entre le concept de Rotter sur le locus de contrôle (1966) et certains aspects de la théorie de Holland (1966). Cent soixante-deux étudiants d'Acadia, tous de sexe masculin, inscrits en première année d'études, ont subi le test Kuder DDsur les motivations occupationnelles (OIS). Le vocations de type primaire ou secondaire, les schémas de comportement conséquents ou inconséquents déterminés pas le test OIS ont été classés selon le système de Holland. Aux niveaux .05 et .01 respectivement, les types intellectuels et réalistes différaient de manière significative des 4 autres types vocationels et cela dans le sens d'un contrôle extérieur plus important.